2013
DOI: 10.1186/1916-0216-42-58
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic rhinitis and asthma in a Northern Alberta cohort

Abstract: BackgroundMany published epidemiologic studies confirm a marked increase in the prevalence of asthma and allergic rhinitis. The link between allergic rhinitis and asthma has been extensively studied and approximately 75% of patients with asthma have allergic rhinitis. The proportion of patients with asthma in populations of allergic rhinitis patients has not been well studied.ObjectiveThe purpose of this study is to estimate the prevalence of undiagnosed asthma in a specific population of patients presenting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…There is evidence showing that patients with AR may have an increased prevalence of bronchial hyper-responsiveness and alterations in the functional testing of breathing. 20 In a study done by Jeffery et al 21 on 107 patients of AR deranged pulmonary function tests were observed in 39.1% of cases and 26.1% of patients were diagnosed with asthma. Our study showed 18 (24.3%) of AR patients had PFT similar to asthma.…”
Section: Discussionmentioning
confidence: 96%
“…There is evidence showing that patients with AR may have an increased prevalence of bronchial hyper-responsiveness and alterations in the functional testing of breathing. 20 In a study done by Jeffery et al 21 on 107 patients of AR deranged pulmonary function tests were observed in 39.1% of cases and 26.1% of patients were diagnosed with asthma. Our study showed 18 (24.3%) of AR patients had PFT similar to asthma.…”
Section: Discussionmentioning
confidence: 96%
“…The total number of inflammatory cells, primarily eosinophils, in the bronchoalveolar lavage fluid (BALF) and pulmonary tissues was increased in OVA-sensitized guinea pigs [ 4 ] and rats [ 5 ]. In addition, the pathogenesis of allergic rhinitis is linked to asthma [ 6 ]. Inhibition of proinflammatory cytokines is effective for controlling and alleviating allergic inflammation because proinflammatory cytokines precede Th2 cytokines in the pathological response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%